The Influence between Self-Efficacy and Resilience on Mathematics Learning Outcomes among Fifth Grade Students - Nugraheni, Intan; Tyas, Dewi Nilam (Lembaga Sosial Rumah Indonesia, 2025)
Purpose – Student learning outcomes are influenced by self-efficacy and resilience. This research aimed to examine how fifth graders at SDN Gugus Sedap Malam in East Semarang District performed in mathematics class based on their resilience and self-efficacy.Method – This quantitative study used a correlational approach. It involved 178 fifth-grade students, with a sample of 65 students selected using proportional sampling. A closed questionnaire with a Likert Scale (four alternative answers) was used via Google Forms, with 30 questions for each variable. Findings – Pearson correlation results showed a significant relationship between self-efficacy and mathematics learning outcomes (r = 0.629, p < 0.001), and resilience and mathematics learning outcomes (r = 0.696, p < 0.001). The r_count value (0.748) being higher than r_table (0.244) indicates a strong relationship between self-efficacy and resilience and mathematics learning outcomes. An R² value of 0.559 (55.9%) was obtained, indicating that self-efficacy and resilience contributed 55.9% to mathematics learning outcomes. This means higher self-efficacy and resilience lead to higher mathematics learning outcomes. Conversely, lower self-efficacy and resilience result in lower mathematics learning outcomes. Research Implications – A practical implication is that teachers and schools should develop programs to improve student self-efficacy and resilience. The curriculum can be adjusted to emphasize mental strengthening and student motivation, focusing on cognitive, attitudinal, and psychomotor aspects.